Pengaruh penggunaan handout fisika berbasis thinking aloud pair problem solving terhadap hasil belajar siswa kelas XI SMA N 1 Ranah Batahan Pasaman Barat - Surati Surati; Hufri Hufri (PILLAR OF PHYSICS EDUCATION, 2019)
Result learn of student interest of SMA N 1 Ranah Batahan not yet is matching with the one which expected. This matter seen at result learns of student interest most not yet reached KKM. This Research aims to investigate the influence of usage of physics handout base on thinking aloud pair problem solving to result learn of class student interest of XI SMA N 1 Ranah Batahan Pasaman Barat. This Type Research is experiment quasi designed by the research of design only group control randomized. Technique intake of the sample the used is sampling purposive because gone to the teacher in school only teaching two class that is a class so that both classes assumed homogeneous and normal to be is up to the standard of the sample which is representative. The interest which is evaluated in this research is attitude, knowledge, and skill domain. Domain attitude instrument the used is observation sheet, knowledge domain instrument use problem in form of a double helix, and skill domain instrument use score rubric. The result of obtained by data analysis is research having taken steps indicate that mean assess higher experiment class from at class control at attitude and skill domain. While at domain knowledge of higher control class. So that can be concluded that there is influence meaning usage of physics handout base on thinking aloud pair problem solving to result learn of class student interest of XI SMA N 1 Ranah Batahan Pasaman Barat at attitude and skill domain.